PENGARUH PENGUASAAN AKUNTANSI DAN INOVASI WIRAUSAHA TERHADAP KINERJA MANAJERIAL PADA PERUSAHAAN JASA DI KOTA MANADO (STUDI PADA BIRO PERJALANAN TRAVEL DI KOTA MANADO) - Herman, Giovani; Elim, Inggriani; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Recent developments in the economy in Indonesia have led to an increasingly increasing accounting role that demands accounting that can provide the financial information needed by society in making economic decisions. It is now increasingly recognized by entrepreneurs. Accounting also greatly facilitates the smoothness of management tasks. This research was conducted at 30 travel agency service companies (travel) located in Manado city. The purpose of this research is to examine the influence of the mastery of accounting and entrepreneurial innovation on managerial performance in travel agency services company in Manado city. The analytical method used is multiple linear regression analysis method with the help of SPSS 12.0 software. Based on multiple linear regression analysis. The result of the research shows that Accounting Mastery (X1) has an effect on Managerial Performance (X2) in Travel Service Company in Manado City, and Entrepreneurial Innovation also has an effect on Managerial Performance in Service Company of Travel Bureau in Manado City. This shows that the variable of Accounting Mastery (X1) and Entrepreneurial Innovation (X2) together have a significant influence on Managerial Performance variables (Y). at Travel Service Company (Travel) in Manado City. so it can be concluded that Ha accepted and rejected H0 or can be said that the variable of Accounting Mastery and Entrepreneurial Innovation Variables affect the variable of Managerial Performance in Travel Service Company (Travel) d Manado City.Keywords: Accounting, Innovation, Entrepreneurship, Managerial Performance